Factors related to feeding of formula milk in infant 0-6 months in West Pamulang, Southern Tangerang City - Osa Marfina Lova; Debby Endayani Safitri; Indah Yuliana (ARGIPA (Arsip Gizi dan Pangan), 2019)
Infant mortality according to WHO is caused by multifactors, one of which is the failure of exclusive breastfeeding. One of the factors causing failure in exclusive breastfeeding is formula feeding. This study uses a cross-sectional design to find out the factors related with the formula feeding of the infants aged 0-6 months. The subjects of this study were mothers who had babies aged 6-12 months with total number of 101 people. The factors studied were knowledge, age, occupation, education, number of children, access to information, family income, family support, childbirth assistance and the place of delivery. The results showed that there was a relationship between knowledge, age, access to information, family income, and family support with the formula feeding of the infants aged 0-6 months. Keywords: Exclusive breastfeeding, Formula Milk